Sharia Economics Edugame (SEE): Alternatif Pengembangan Pemahaman Literasi Keuangan Syariah - Muhammad Al Faridho (LP2M IAIN Palangka Raya, 2018)
The recent Sharia economics education is now developed both theoretically and practically. Ironically, the fast development of sharia economics education is not accompanied with the development of understanding on sharia finance literacy. Researches are interested in conducting studies by offering an application of education game released as a prototype of Sharia Economics Edugame (SEE). This study applies quantitative method using Technology Acceptance Model (TAM) approach through Structural Equation Modeling (SEM). This model is used to determine the effect of the game towards the students' interest to learn understanding of sharia finance literacy. The sampling technique used in this study is purposive sampling, by taking 100 respondents of students who concerned on Sharia finance. The findings revealed that SEE prototype test with TAM variable increase their understanding on sharia finance literature.